Penerapan Teknologi Tepat Guna Mesin Pemipih Emping Untuk Meningkatkan Produktivitas Perajin Emping Di Sumberadi, Mlati, Sleman - Eka Sulistyaningsih; Aris Budi Mulyono; Nur Adinda Guswantoro; Adinda Arum Tirta Melati; Shefina Herawati (Jurnal Abdimas Madani dan Lestari (JAMALI), 2023)
Emping melinjo is a processed product from melinjo whose manufacturing process is by flattening old melinjo fruit which was previously roasted. In the process of making melinjo chips, which is quite time consuming and tiring, is the flattening process. The purpose of this activity is to make a chipping flattening machine to increase the productivity of cracker craftsmen. The chip flattening machine uses a pressing system to optimize the productivity of the melinjo chips home industry in Sumberadi, Sleman..The chip flattening machine uses a driving motor in the form of an electric motor with specifications of HP and an angled iron as the frame.Before being handed over to partners, the machine has been tested for several times at the Materials Testing Laboratory of the AKPRIND Institute of Science & Technology, Yogyakarta.In this test, it was found that the process of flattening melinjo seeds for making chips only takes 10 seconds.It is much more effective than manual creation which takes 3 minutes.In addition, the number of chips produced in the same period of time using the machine will be more than the manual process.